Chronic Obstructive Pulmonary Disease in Cameroon: Prevalence and Predictors—A Multisetting Community-Based Study - Massongo Massongo; Adamou Dodo Balkissou; Laurent-Mireille Endale Mangamba; Virginie Poka Mayap; Marie Elisabeth Ngah Komo; Abdou Wouoliyou Nsounfon; Alain Kuaban; Eric Walter Pefura Yone (Pulmonary Medicine)
Objective. Little is known concerning chronic obstructive pulmonary disease (COPD) in Sub-Saharan Africa (SSA), where the disease remains underdiagnosed. We aimed to estimate its prevalence in Cameroon and look for its predictors. Methods. Adults aged 19 years and older were randomly selected in 4 regions of Cameroon to participate in a cross-sectional community-based study. Data were collected in the participant’s home or place of work. Spirometry was performed on selected participants. COPD was defined as the postbronchodilator forced expiratory volume in 1 second/forced vital capacity ratio FEV1/FVC<lower limit of normal, using the global lung initiative (GLI) equations for Black people. Binomial logistic regression was used to seek COPD-associated factors. The strength of the association was measured using the adjusted odds ratio (aOR). Results. A total of 5055 participants (median age (25th-75th percentile) = 43 (30–56) years, 54.9% of women) were enrolled. COPD prevalence (95% confidence interval (95% CI)) was 2.9% (2.4, 3.3)%. Independent predictors of COPD (aOR (95% CI)) were a high educational level (4.7 (2.0, 11.1)), living in semiurban or rural locality (1.7 (1.4, 3.0)), tobacco smoking (1.7 (1.1, 2.5)), biomass fuel exposure (1.9 (1.1, 3.3)), experience of dyspnea (2.2 (1.4, 3.5)), history of tuberculosis (3.6 (1.9, 6.7)), and history of asthma (6.3 (3.4, 11.6)). Obesity was protective factor (aOR 95%CI=0.3 (0.2, 0.5)). Conclusion. The prevalence of COPD was relatively low. Alternative risk factors such as biomass fuel exposure, history of tuberculosis, and asthma were confirmed as predictors.